Knowledge of Islamic Cultural History and Religious Moderation: Correlation Studies on Students of State Aliyah Madrasah Bekasi - Suhardin Suhardin; Nurhayati Nurhayati; Rabiathul Adawiyah (STAI Hubbulwathan Duri, 2022)
High-ranking state officials who assert that Islamic history is inextricably linked to war will be able to ignite radicalization among millennials, harassing researchers to demonstrate empirically. This study aims to ascertain whether there is a correlation between students' knowledge of Islamic cultural history and their religious moderation at State Aliyah Madrasah Bekasi. The research technique used was a quantitative associative correlation with a sample size of one hundred randomly selected respondents. The study's findings indicated a highly significant correlation between students' knowledge of Islamic cultural history and religious moderation. As a result of these findings, it can be concluded that the history of Islamic culture has an effect on millennials' religious moderation. To increase millennial moderation, millennials' knowledge of Islamic cultural history must be increased. Thus, the history of Islamic culture must be preserved as a subject, and content concerning war must be explained objectively and accurately to ensure that teenagers understand their religion correctly and accurately.